2009
DOI: 10.1080/10629360903408423
|View full text |Cite
|
Sign up to set email alerts
|

A QCAR model for predicting antioxidant activity of wild mushrooms

Abstract: Wild mushrooms have been described as sources of natural antioxidants, particularly phenolic compounds. However, many other compounds present in wild mushrooms can also act as antioxidants (reducers), so whole extracts from a wide range of species need to be examined. To gain further knowledge in this area, the relationship between the antioxidant potential (scavenging effect and reducing power) and chemical composition of twenty three samples from seventeen Portuguese wild mushroom species was investigated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Lee et al (2001) tested the amino-polysaccharide fraction from G. lucidum for the ability to protect against oxidative damage induced by reactive oxygen species and found that this fraction significantly inhibited iron-or iron plus ascorbic acid-induced lipid peroxidation in the rat brain homogenates 64.2% at highest concentration (2 mg/mL) and showed a dose-dependent inactivation of hydroxyl radicals and superoxide anions. Antioxidant activity of mushrooms is mainly related to their content in phenolic compounds (Froufe et al, 2009), which is also typical for olives, olive oil and leaves (Benavente-García et al, 2000). Oleuropein, the major constituent of the secoiridoid family in the olive trees, has been shown to be a potent antioxidant.…”
Section: Fatty Acid Composition Of Tissues and Oxidative Status Of Ramentioning
confidence: 99%
See 1 more Smart Citation
“…Lee et al (2001) tested the amino-polysaccharide fraction from G. lucidum for the ability to protect against oxidative damage induced by reactive oxygen species and found that this fraction significantly inhibited iron-or iron plus ascorbic acid-induced lipid peroxidation in the rat brain homogenates 64.2% at highest concentration (2 mg/mL) and showed a dose-dependent inactivation of hydroxyl radicals and superoxide anions. Antioxidant activity of mushrooms is mainly related to their content in phenolic compounds (Froufe et al, 2009), which is also typical for olives, olive oil and leaves (Benavente-García et al, 2000). Oleuropein, the major constituent of the secoiridoid family in the olive trees, has been shown to be a potent antioxidant.…”
Section: Fatty Acid Composition Of Tissues and Oxidative Status Of Ramentioning
confidence: 99%
“…Medicinal mushrooms have a proven antioxidant effect and are therefore a suitable supplement to reduce the risk of oxidation. Many studies prove that they contain a number of potential natural antioxidants (Cheung et al, 2003;Cheung and Cheung, 2005;Lindequist et al, 2005) and are also a good source of phenols, flavonoids, carotenes and ascorbic acid (Froufe et al, 2009). They have an established history of use in the traditional medicine, particularly in Asia.…”
mentioning
confidence: 99%
“…Our research group has performed studies of radical‐scavenging capacity, reducing power, and inhibition of lipid peroxidation in more than 30 different species (Barros and others 2007, 2008a, 2008b; Ferreira and others 2007; Heleno and others 2010). In most of these studies, it was possible to observe significant correlations between phenolics concentration and antioxidant activity, proved by a QCAR (Quantitative Composition‐Activity Relationships) model (Froufe and others 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In modern food processing industry there can be found use of physical properties of food together with chemometric tools (Bajoub et al, ; Dodić et al, ; Gosetti, Chiuminatto, Mazzucco, Mastroianni, & Marengo, ; Jevrić et al, ). A QCAR (quantitative composition–activity relationship) model was constructed for the antioxidant content prediction of wild mushrooms (Froufe, Abreu, & Ferreira, ). Total antioxidant capacity of onion ( Allium cepa ) and shallot ( Allium oschaninii ) was determined through PLSR approach and cluster analysis [principal component analysis (PCA)] and discriminant function analysis (DFA) differentiated varieties of onions and shallot (Lu et al, ).…”
Section: Introductionmentioning
confidence: 99%